2020
DOI: 10.1089/apc.2019.0219
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Patient HIV Risk by Primary Care Providers in High-HIV Prevalence Areas in the Southern United States

Abstract: The southern United States accounted for 52% of new HIV diagnoses in 2015. Visits to primary care providers (PCPs) offer opportunities for routine HIV screening. However, of at-risk persons in the United States who visited a health care provider within the previous year, >75% were not offered a test for HIV. Perceptions of patient population risk by PCPs could offer insight into these missed opportunities, and inform development of HIV testing interventions for PCPs to increase routine screening. During April-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Finally, this analysis did not cover several other sources of disparities in PrEP access, such as socioeconomic status, state policies, or health care provider attitudes or knowledge. 25,26,55,56 In conclusion, although PrEP has been transformative, and its use has been on the rise, significant challenges in its implementation remain. This study revealed that PrEP was under-prescribed to individuals who were at the highest risk for HIV acquisition (13-25 years old, black people, women, in the southern United States).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this analysis did not cover several other sources of disparities in PrEP access, such as socioeconomic status, state policies, or health care provider attitudes or knowledge. 25,26,55,56 In conclusion, although PrEP has been transformative, and its use has been on the rise, significant challenges in its implementation remain. This study revealed that PrEP was under-prescribed to individuals who were at the highest risk for HIV acquisition (13-25 years old, black people, women, in the southern United States).…”
Section: Discussionmentioning
confidence: 99%
“…Although the goal of screening more than 80% of US adults for HIV is aspirational, research demonstrates that increased screening in health care settings would be cost effective, even for lower-risk groups, 6 and is key to ending the HIV epidemic. 4 Barriers to HIV testing in primary care settings include health care providers' unfamiliarity with national recommendations, 7,8 continued preference for risk-based screening, 8 assumptions about risk, 9 and HIV stigma. 9 However, studies have shown that improved HIV-testing uptake is possible using interventions such as patient text message reminders 10 and provider electronic medical record prompts.…”
Section: Discussionmentioning
confidence: 99%
“…4 Barriers to HIV testing in primary care settings include health care providers' unfamiliarity with national recommendations, 7,8 continued preference for risk-based screening, 8 assumptions about risk, 9 and HIV stigma. 9 However, studies have shown that improved HIV-testing uptake is possible using interventions such as patient text message reminders 10 and provider electronic medical record prompts. 11 For example, a 2-fold increase in HIV screening was achieved using a passive electronic medical record reminder at a hospital based, academic primary care practice.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although low reporting rates might reflect the perception that patients are at low risk of HIV infection, assessment of risk may be inaccurate. 6 Further, the rising prevalence of hepatitis C infection heightens the concern for transmission of infection during occupational exposures. 7 Lack of time and cumbersome processes were noted, similar to those reported from other surgical trainees.…”
Section: Discussionmentioning
confidence: 99%